Virtuality in the time of pandemic from the topographic engineering education perspective (Revista Electrónica Calidad en la Educación Superior, 2022)
This article tries to expose the topographic engineering degree, from the University of Costa Rica, professors’ experience regarding changing to virtual education because of the Covid-19 pandemic. A semi-structured qualitative instrument was applied for collecting information. The instrument was responded to 24 teachers, and it was answered in July 2021 Technical difficulties, deterioration of mental health, from virtual education were the main results.
Keywords: Virtual Education; Advantages; Disadvantages